Practical Exploration of Digital Governance in Smart Apartment Communities from the Perspective of Data Interoperability - Liu, Han (Innovation in Science and Technology, 2025)
In the context of accelerating urbanization, the frequent mobility of residents in apartment communities poses significant challenges to traditional governance models, such as large personnel turnover and difficulties in service coordination. This study focuses on the digital governance of smart apartment communities, exploring the technical implementation and application value of data interoperability between “apartment management systems and community governance platforms”. Taking the integration practice of the independently developed “Tenant Information Intelligent Filing System” and the community governance platform as a case study, this paper in-depth analyzes the key technologies and security standards of data interface development, and demonstrates the actual effectiveness of the digital governance model in improving tenant filing efficiency and shortening safety hazard response time. The results indicate that through data interoperability technology, information silos can be effectively broken down, community governance processes can be optimized, and governance efficiency can be enhanced, providing practical references and theoretical support for the governance of new-type urban communities.